EFFECT OF PREPARATION METHOD OF Ni CATALYST USING BENTONITE AS THE SUPPORT MATERIAL - Hery Haerudin; Silvester Tursiloadi; Galuh Widiyarti; Wuryaningsih Sri Rahayu (Indonesian Journal of Chemistry, 2003)
Nickel catalyst has been prepared impregnation and precipitation with nickel content of 20% and 25% each using bentonite as support material. The effects of the preparation method were studied using temperature programmed oxidation (TPO) and temperature programmed reduction (TPR) and by determination of its specific surface area. The activity of catalysts has been tested in the hydrogenation of palm oil. The catalyst with 20% of nickel and prepared by impregnation shows a single peak at 301°C, compared to catalyst with 25% of nickel prepared by the same method which has a peak at 304°C and a shoulder at 330°C. The reduction curves of both catalysts, those are prepared by impregnation, show a homogeneity indicated by a high main peak at 426°C (20% Ni) and 430°C (25% Ni). The 25% nickel catalyst by impregnation has a shoulder at 508°C. The catalysts prepared by precipitation show peaks at 508°C and 661°C for 20% of Ni and peaks at 419°C and 511°C for 25% of Ni. The reduction curves of catalysts prepared by precipitation are significantly different from each other. Those are also very different comparing to the reduction curve of impregnated catalyst. The 20% precipitated nickel catalyst has a single peak at 540°C, but the 25% precipitated nickel catalyst shows peaks at 346°C and 503°C. The differences of peak position among the reduction curves of catalysts resulted in the differences of catalyst activities with the following order 20% Ni (impregnation) > 25% Ni (impregnation) > 20% Ni (precipitation) > 25% Ni (precipitation).